The future of direct payments system in the EU agriculture; European Commission scenarios - Krzyżanowski, Julian (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
The paper deals with the future of direct payments system in the EU agriculture. Different scenarios of the current system adjustments, as proposed by the European Commission, are presented. Four possible scenarios are being discussed: An ‘EU flat rate’, a pragmatic approach, the use of objective criteria and a combination of a pragmatic approach and objective criteria. It seems that the best option for the New Member States are the flat rate or the pragmatic approach criteria.